2017
DOI: 10.3390/catal7010017
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochlorination of Acetylene Catalyzed by an Activated Carbon-Supported Ammonium Hexachlororuthenate Complex

Abstract: Ammonium hexachlororuthenate ((NH 4 ) 2 RuCl 6 ) complex was used as a catalyst precursor and coconut activated carbon (AC) was used as the support in the preparation process of the Ru-based catalyst. (NH 4 ) 2 RuCl 6 /AC catalyst was prepared via an incipient wetness impregnation method and assessed in an acetylene hydrochlorination reaction. Meanwhile, the (NH 4 ) 2 RuCl 6 /AC catalyst was analyzed with low-temperature N 2 adsorption/desorption, thermogravimetry (TG), transmission electron microscopy (TEM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…1 ). 75 Combined with the HCl-TPD and C 2 H 2 -TPD data, it is well shown that the incorporation of ChCl can improve the adsorption ability of the Pd@USY catalyst to both the HCl and C 2 H 2 reactants, which is beneficial to the catalytic reaction. Moreover, C 2 H 3 Cl-TPD experiments were performed to further study the effect of the presence of ChCl ligand on the adsorption ability of C 2 H 3 Cl product.…”
Section: Resultsmentioning
confidence: 87%
“…1 ). 75 Combined with the HCl-TPD and C 2 H 2 -TPD data, it is well shown that the incorporation of ChCl can improve the adsorption ability of the Pd@USY catalyst to both the HCl and C 2 H 2 reactants, which is beneficial to the catalytic reaction. Moreover, C 2 H 3 Cl-TPD experiments were performed to further study the effect of the presence of ChCl ligand on the adsorption ability of C 2 H 3 Cl product.…”
Section: Resultsmentioning
confidence: 87%
“…Although the catalyst prepared via cation exchange Ru/G60 5%(CE) exhibited a lower conversion (35%) than the one prepared by the SI method (40.4%), it allowed achieving the highest selectivity and yield toward epoxidation products. The higher stability of the metallic precursor (NH 4 ) 2 RuCl 6 used in the cation exchange method compared to RuCl 3 used in sol immobilization may also contribute to reducing the aggregation of Ru particles during the reaction . That could be a hypothesis for the lower Ru particle size and higher catalytic activity of the former catalyst after 6 h of reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The higher stability of the metallic precursor (NH 4 ) 2 RuCl 6 used in the cation exchange method compared to RuCl 3 used in sol immobilization may also contribute to reducing the aggregation of Ru particles during the reaction. 58 That could be a hypothesis for the lower Ru particle size and higher catalytic activity of the former catalyst after 6 h of reaction.…”
Section: Cation Exchange (Ce)mentioning
confidence: 99%
“…Polar selective adsorption materials are widely used in practical production because of their simple and convenient synthesis method, recyclability, and high economic value. The main representatives of these materials are activated carbon, alumina, molecular sieve, etc., which are characterized by ultra-high pore size, specific surface area, and surface degree points [23]. Thus, they are widely used in waste gas treatment, wastewater treatment, and other fields.…”
Section: Polarity Selective Adsorbentmentioning
confidence: 99%